Prevalence of Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus in Retail Ready-to-Eat Foods in China - Yang, Xiaojuan; Zhang, Jumei; Yu, Shubo; Wu, Qingping; Guo, Weipeng; Huang, Jiahui; Cai, Shuzhen (Frontiers in Microbiology, 2016)
Staphylococcus aureus, particularly methicillin-resistant S. aureus (MRSA), is a life-threatening pathogen in humans, and its presence in food is a public health concern. MRSA has been identified in foods in China, but little information is available regarding MRSA in ready-to-eat (RTE) foods. We aimed to investigate the prevalence of S. aureus and MRSA in Chinese retail RTE foods. All isolated S. aureus were tested for antimicrobial susceptibility, and MRSA isolates were further characterized by multilocus sequence typing (MLST) and staphylococcal cassette chromosome mec (SCCmec) typing. Of the 550 RTE foods collected from 2011 to 2014, 69 (12.5%) were positive for S. aureus. Contamination levels were mostly in the range of 0.3–10 most probable number (MPN)/g, with five samples exceeding 10 MPN/g. Of the 69 S. aureus isolates, seven were identified as MRSA by cefoxitin disc diffusion test. Six isolates were mecA-positive, while no mecC-positive isolates were identified. In total, 75.8% (47/62) of the methicillin-susceptible S. aureus isolates and all of the MRSA isolates were resistant to three or more antibiotics. Amongst the MRSA isolates, four were identified as community-acquired strains (ST59-MRSA-IVa (n=2), ST338-MRSA-V, ST1-MRSA-V), while one was a livestock-associated strain (ST9, harboring an unreported SCCmec type 2C2). One novel sequence type was identified (ST3239), the SCCmec gene of which could not be typed. Overall, our findings showed that Chinese retail RTE foods are likely vehicles for transmission of multidrug-resistant S. aureus and MRSA lineages. This is a serious public health risk and highlights the need to implement good hygiene practices.